Solution of heat equation stationary problem - Makovetska, Svetlana; Seidykh, Olga; Fomenko, I. (My University, 2015)
This paper aims to propose the use of information technology in solving problems of mathematical physics. The paper describes the software implementation of the solution for heat equation with the use of MathCAD mathematical package. Benefits of using information technology in solving different problems of mathematical physics were analyzed in comparison with traditional methods during university course. The specificity of combination of mathematical physics problems and built-in functions of MathCAD environment makes it possible to operate with no cumbersome expressions. Promising area of future research is methodical, mathematical and algorithmic aspects of efficient software implementations of numerical methods within MathCAD environmemt.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; MathCAD; обчислення похідних; рівняння теплопровідності; вбудовані функції